HUBUNGAN PENGETAHUAN TENTANG KEANEKARAGAMAN PANGAN DENGAN STATUS GIZI IBU HAMIL - Silaban, Grace Miranda; Hastuty, Yulina Dwi (Colostrum Jurnal Kebidanan, 2021)
Nutrition for pregnant women is food in the form of macronutrients and micronutrients needed by mothers during pregnancy, and good knowledge is an important domain for mothers because it affects maternal actions in providing adequate nutrition for pregnant women to avoid chronic energy deficiency in pregnant women. This study aims to determine the correlation between knowledge about food variety and the nutritional status of pregnant women in the village of Laluan Lama and Marindal I in 2021.This study was correlational with a cross sectional design. Sampling using total sampling technique with a population of 35 people and a sample of 35 people. Collecting data using a questionnaire, data analysis using the chi square test.The results showed that most of the respondents were in early adulthood (62.9%), had secondary education (68.6%), worked as housewives (74.3%), and with family income < Deli Serdang’s regional minimum wage (91.4). %). Distribution of pregnant women who have good knowledge (54.3%) and poor knowledge of mothers (45.7%), while pregnant women who have good nutritional status (68.6%) and poor nutritional status (31.4%). There was correlation between mother's knowledge about food variety and the nutritional status of pregnant women in Laluan Lama and Marindal I Villages in 2021 with p-value = 0.011.It is necessary to increase knowledge of mothers about food diversity which can be done through providing information on meeting the nutritional needs of pregnant women to reduce the number of undernutrition status in pregnant women.